The role of unpasteurized hawked milk in the transmission of brucellosis in Eldoret municipality, Kenya - Augustine Taban Namanda; Rose Kakai; Mary Otsyula (Journal of Infection in Developing Countries)
Background: Brucellosis is a zoonotic disease that continues to infect many people worldwide. Though its mortality rate is low, long convalescent periods associated with brucellosis translate into reduced socio-economic capacity of the people affected. Human brucellosis is mostly transmitted from animals. In Kenya, the prevalence of the disease has increased recently, along with the increased hawking of unpasteurized milk. The extent of the risk such raw milk poses to human health with respect to brucellosis is unknown. This study investigates the possibility of brucellosis being transmitted through unprocessed milk sold by hawkers in Eldoret municipality. Methodology: In this cross-sectional study, 130 samples of unpasteurized pooled milk from hawkers and 14 pasteurized milk samples were collected from shops in selected estates using cluster and simple random sampling techniques. All samples were subjected to the Brucella Milk Ring Test (MRT) for screening. A milk consumption questionnaire was administered to households in the selected estates to establish their milk sources and consumption patterns. Data analysis involved comparing computed percentages of different variables. Results: A high proportion of households (77.5%) consume unpasteurized milk from hawkers. However, no antibody to Brucella was detected in any of the milk samples collected. Conclusion: We find no evidence that hawked milk in Eldoret is responsible for transmitting brucellosis to consumers. More research in the potential transmission of brucellosis through milk consumption is recommended.